Radio in the Midst of Technological Development and New Media: Case Study of Delta FM Broadcasting Segment "Siaran Lagu Cinta" - Putri Surya Cempaka (2020)
This article discussed radio broadcasting technology in general and how the industry is relatively resilient amid the development of other media technologies today, such as the Internet. Internet technology is able to present number of social networks through social media that are interactive, direct, and user generated. In addition, the Internet forces conventional broadcasting industries such as radio to penetrate digital mechanisms by practicing radio streaming. Radio broadcasting also add this type of interaction to their listeners, for example through websites, blogs, vlogs (video blogs), Twitter, Instagram, Snapchat, and Facebook accounts. This integrated conventional media technology and new media is often called media convergence. By using qualitative approach and descriptive method, this paper explained a case of media convergence by one of the radio broadcast station in Indonesia that is Delta FM. As a result, Delta FM presents its broadcasts with the help of new media in order to survive in the broadcasting industry amid the current widespread use of new media.